Two cycles of adjuvant carboplatin in stage I seminoma: 8-year experience by the Hellenic Cooperative Oncology Group (HECOG) - Koutsoukos, K.; Tzannis, K.; Christodoulou, C.; Karavasilis, V.; Bakoyiannis, C; Makatsoris, T.; Papandreou, C.N.; Pectasides, D.; Dimopoulos, M.A.; Bamias, A. (World Journal of Urology, 2016)
Purpose: Following the establishment of adjuvant carboplatin in stage I testicular seminoma as a standard, we adopted this treatment for all stage I seminoma patients. We report our 8-year experience and compare these results with our previous adjuvant etoposide/cisplatin (EP) strategy. Patients and methods: Patients with stage I seminoma, treated with adjuvant carboplatin and with a minimum follow-up of 1 year, were included. Two cycles of carboplatin [area under the curve (AUC) 6] were administered. Results: A total of 138 patients with median age of 34 years, treated from September 2003 to December 2011, were selected. There were 5 relapses [5-year relapse-free rate (RFR) 96.8 % (95 % confidence interval 91.6–98.8)]: 3 relapses at retroperitoneal lymph nodes, 1 relapse at the adrenal gland, and 1 isolated brain metastasis. Four patients with relapse were cured with salvage chemotherapy. All patients with relapse had tumor diameter ≥4 cm and/or age ≤34 years. Patients with at least 1 of the above risk factors (n = 111) had a significantly higher relapse rate compared with a similar population (n = 64) treated with 2 cycles of adjuvant EP: 5-year RFR was 95 % (SE 2 %) versus 100 % (SE 0 %), (p = 0.067). Conclusions: Age and tumor diameter were associated with relapse in stage I seminoma treated with adjuvant carboplatin. Although adjuvant carboplatin in patients with age ≤34 and/or tumor diameter ≥4 cm is associated with higher relapse rates than EP, the prognosis of these patients is excellent, and therefore, the use of less toxic treatment is justified. © 2015, Springer-Verlag Berlin Heidelberg.
Keywords: Seminoma; Stage I; Two cycles of carboplatin